Answer:
C
Step-by-step explanation:
Given the 2 equations
x + 2y = 1.5 → (1)
2x + y = 1.5 → (2)
Rearrange (1) expressing x in terms of y by subtracting 2y from both sides
x = 1.5 - 2y → (3)
Substitute x = 1.5 - 2y in (2)
2(1.5 - 2y) + y = 1.5 ← distribute left side
3 - 4y + y = 1.5
3 - 3y = 1.5 ( subtract 3 from both sides )
- 3y = - 1.5 ( divide both sides by - 3 )
y = 0.5
Substitute y = 0.5 into (3) for corresponding value of x
x = 1.5 - (2 × 0.5) = 1.5 - 1 = 0.5
Solution is x = 0.5 and y = 0.5 → C